REVIEW OF SOME LESSER KNOWN MEMBERS OF ZINGIBERACEAE FAMILY - Dr. Jyoti Hajong; Rosy Gupta (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: The Zingiberaceae family, commonly known as the Ginger family, comprises 53 genera and more than 1300 species distributed throughout tropical Africa, America, and Asia, several important genera including curcuma, kaempferia, hedychium, gastrochilus, amomum, zingiber, costus, elettaria, alpinia, maranta, canna and musa. The members of Zingiberaceae family have been used for centuries in various traditional medicine systems such as Ayurveda, Traditional Chinese Medicine, and Unani medicine. The plants of this family hold significant importance across multiple domains such as medicine, culinary arts, economic impact, cultural practices and environmental contributions are not the less important. Aim: The article focuses some lesser explored plants of this family, the characters and properties of Sthulagranthi (Zingiber zerumbet Rosc.), Karchura (Curcuma zedoaria Rosc.), Kalihaldi (Curcuma caesia Roxb.) and Amahaldi (Curcuma amada Roxb.) are discussed here in the present article. Materials and methods: For this article the data were scrutinized from the texts of botany, classical Ayurvedic texts, as well as databases from Pubmed, Google Scholar, Research Gate and other online sources. Discussion: Since all these plants share some synonyms and morphological features, confusion and difficulty arise in their identification. But they also bear some distinctive characters also, which are highlighted in the present article. Conclusion: Mostly these drugs are having distinct therapeutic effects on respiratory disorders like Kasa, Swasha, Hikka, etc.; skin disorders like leucoderma, prurigo, leprosy, etc.; carminatives, appetizers, useful in peptic ulcers, stomach-ache, piles, etc.